Sistem Pakar Pertumbuhan Dan Perkembangan Pada Tanaman Cabai Dengan Metode Forward Chaining - Eva Itma Anna; Hamdan Sukri; Herwan Yudiarto (Jurnal Teknologi dan Informatika (JEDA), 2022)
Expert System based on knowledge about chili disease by utilizing Forward Chaining method is an application that can be used to provide knowledge about chili disease. to farmers can easy to use this application to find out the types of diseases that exist in the his chili garden. methode forward chaining a question description advance makes it easier for farmers to choose the characteristics of chili diseases in their gardens. With this application, farmers will be able to be ready and agile in dealing with plantation problems. This application is made in the base website so that it can be accessed via their respective smartphones. This system in taste can provide answers to plantation problems by replacing the role of plant experts and chili diseases. but in its implementation the role of a Experts cannot be replaced directly by the system. so this application actually can only give advice to farmers to act fast, but to be sustainable there needs to be an application that can be done in real time.